2018
DOI: 10.1103/physrevlett.121.263901
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Index Bound States in the Continuum

Abstract: Metamaterials with an effective zero refractive index associated to their electromagnetic response are sought for a number of applications in communications and nonlinear optics. A promising way that this can be achieved in all-dielectric photonic crystals is through the design of a Dirac cone at zero Bloch wave-vector in the photonic band structure. In the optical frequency range, the natural way to implement this design is through the use of a photonic crystal slab. In the existing implementation, however, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 31 publications
1
90
0
Order By: Relevance
“…Yet, in principle, spectral isolation is not necessary for the existence of localized bound states. In fact, bound states that coexist with degenerate extended ones, commonly known as bound states in the continuum (BICs), have been found across a variety of other physical systems, including quantum systems [30][31][32][33], water waves [34][35][36][37][38][39], acoustics [40][41][42][43][44][45], and photonics [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
mentioning
confidence: 99%
“…Yet, in principle, spectral isolation is not necessary for the existence of localized bound states. In fact, bound states that coexist with degenerate extended ones, commonly known as bound states in the continuum (BICs), have been found across a variety of other physical systems, including quantum systems [30][31][32][33], water waves [34][35][36][37][38][39], acoustics [40][41][42][43][44][45], and photonics [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
mentioning
confidence: 99%
“…Over the last decade, it was shown that optical bound states with suppressed radiation loss may exist within the radiation continuum in open resonators [12][13][14][15][16][17][18][19][20][21][22]. These excitations are known as "embedded eigenstates", in analogy with the spatially localized electron states with "positive energy" in quantum systems [23][24][25].…”
Section: Main Textmentioning
confidence: 99%
“…One of the useful techniques to realize the phase shifters is using Photonic Crystal (PC) metamaterials. It is represented that PC metamaterials can tune the photonic dispersion so that one can build new optical devices with new functionalities [3,4,8,[10][11][12][13][14][15][16][17]. In fact, PC metamaterials could be built in a way which exhibit Dirac-cone photonic dispersion in the center of Brillouin-Zone in an arbitrary frequency using the concept of accidental degeneracy [15].…”
Section: Introductionmentioning
confidence: 99%